Penerapan 2 SLS GMM-AB pada Persamaan Simultan Data Panel Dinamis untuk Pemodelan Pertumbuhan Ekonomi Indonesia sebagai Islamic Country - Shina, Arya Fendha Ibnu (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2016)
Indonesia is an islamic country that still has problems in economics such asunemployment and poverty. Stability and economic growth are expected toovercome these problems. Two-way relationship between unemployment and economic growth can be summarized in a system of simultaneous equation. Two directions relationship of mutual influence can be summarizedin a system of simultaneous equations. Economic variables are dynamic; the value is influenced by value of variable itself in the past and also the value of other variables. In a dynamic panel data model there is a lag of the dependent variable that causes the OLS estimates can be biased and inconsistent. Arellano-Bond GMM with optimal weight produces parameter estimate which is unbiased, consistent, and efficient. From this study we can conclude that there is a simultaneous relationship between economic growth and unemployment. If economic growth increases 1%, it will cause the unemployment decrease to 0.956% in short-term and 0.988% in shortterm. On the other hand, if unemployment increases 1%, it will cause a slowdown in economics to 0.465% and 0.615% for the long term